The Digital Interaction of Generation Z: Communication Patterns with Idols Through TikTok Live Streaming - Mochammad Muchlis Romadon; Afnan Karimah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research examines the digital interaction patterns of Generation Z with their idols through live streaming on TikTok. As a generation deeply connected to digital technology, Generation Z spends a significant amount of time on social media platforms, with TikTok being one of the most popular choices due to its interactive live streaming feature. This study aims to explore how real-time communication during live streaming influences the parasocial relationship between fans and idols. Using a descriptive qualitative approach, data was collected through online participatory observation, in-depth interviews, and documentation. A total of 12 participants aged 18 to 23 who actively followed live streaming sessions on TikTok were involved in this research. The study results revealed that 75% of participants felt emotionally closer to their idols during live streaming compared to pre-recorded content. The main interaction patterns observed included personal comments and questions, as well as the use of interactive features such as sending virtual gifts, which allowed fans to receive direct recognition from their idols. These interactions strengthened the emotional bond between fans and idols. The study also found that the idol's personality and responsiveness significantly influenced fan engagement. More interactive and responsive live sessions tended to sustain fan interest, while longer and less interactive sessions led to a decline in engagement. This research highlights how live streaming technology plays a crucial role in shaping digital communication patterns, particularly in strengthening parasocial relationships between Generation Z and their idols on TikTok. The study provides insights into the dynamics of real-time digital communication and its impact on fan-idol relationships, contributing to a broader understanding of the role of social media in contemporary fan culture.